"Vivo sin vivir en mí": YouTube y la poesía de santa Teresa de Jesús. Issue 1 (2nd January 2016) - López, Josefina C.
ABSTRACT: The poetry of Saint Teresa of Jesus has not aroused the same interest from the critics as has her prose. There are several reasons for this. However, her poetry has remained in the memory of anyone who has come in contact with it, as well as in public manifestations, one of which is the phenomenon of new media—in particular, YouTube. Consequently, this article presents an analysis of Teresa de Jesus's poem "Vivo sin vivir en mí" ("Live without living in me") in the context of new media, specifically YouTube, in order to further analyze the oral-auditory impact of her work as a strategy of representation in the reception of her writing and, therefore, expand the communicative possibilities of her writing style close to the spoken language, beyond her time and context.